E-leadership of the school principals in implementing online learning during COVID-19 pandemic at public senior high schools - Indra, Ristapawa; Ritonga, Mahyudin; Kustati, Martin (Frontiers in Education, 2022)
This research aimed to discover the implementation of e-leadership for school principals during the COVID-19 pandemic and its effect on school performance through changes in teacher behavior. Quantitative research was used where it involved 8 public high schools with 150 respondents. The results showed that: (1) the implementation of e-leadership for school principals during the COVID-19 pandemic was at a very high level for the dimensions of the vision of continuous learning and professional development of teachers, and at a high level for the dimensions of classroom supervision and teacher performance assessment; (2) none of the independent variables have a correlation with the dependent variable greater than >0.50. The correlation between the independent variable and the dependent variable is at a simple stage for teacher behavior and a low stage for teacher performance; (3) the result of measurement model test with Confirmatory Factor Analysis (CFA) shows that the loading factor of each indicator is greater than 0.60, which means that the indicators are valid for measuring the variable; (4) the results of the structural model test show that the principal’s e-leadership variable, scientific competence (pedagogical knowledge and pedagogical content knowledge), personality competence and e-skills have a positive and significant effect on teacher behavior with a value of ***p = < 0.05. Teacher performance also has a positive and significant effect with a value of ***p = < 0.05 which makes H-1–H-9 accepted. Proportionally, e-leadership remains the main variable compared to other variables which gives the largest contribution to improving teacher performance through changes in teacher behavior by (0.280), scientific competence variables (pedagogical knowledge and content knowledge) and teacher personality, respectively, contribute to improved performance through changes in teacher behavior of (0.083) and (0.152). The e-skill competency variable of teachers contributes to increased performance through changes in teacher behavior of (0.177). The practical implication of this research is that principals need to change their roles and leadership styles from conventional to electronic-based learning leadership styles to realize effective online learning.